Role of Diffusion-Weighted MRI ( DWI) in Differentiating Between Benign and Malignant Nodules of Thyroid Taking Histopathology as Gold Standard - Saeed, Zoha Arif; Arooj, Sadaf; Rashid, Nawaz; Masood, Mahjabeen; Asghar, Aisha (Annals of King Edward Medical University, 2023)
Background: Thyroid gland is a principal endocrine organ, first to develop in embryo, endodermal in origin and producing hormones essential for life. It is a vascular organ inclusive of right and left lobes, surrounded by a capsule and isthmus in the centre. Objective: To determine the role of Diffusion-Weighted MRI ( DWI) in differentiating between benign and malignant thyroid nodules keeping histopathology as the gold standard. Methodology: One hundred and three patients (103) were enrolled. DWI sequence was performed on 1.5 Tesla GE machine at b-values of 0, 50 and 1000 s/mm2 with correlative ADC map and quantitative values were calculated. FNAC of the thyroid nodules was carried out and results were tallied with ADC values. Out of these, five patients lost to follow up and an inadequate sample was obtained in six patients. Results: Mean age of patients (n=92) was 39 years. Out of 92 patients, 26 patients (28.3%) showed restricted diffusion on DWI in malignant thyroid nodules. Mean ADC ( Apparent Diffusion Coefficient) value of benignthyroid nodules (1.43 × 10-3mm2s-1) was significantly greater than malignant thyroid nodules (0.91×10-3mm s-1). For discriminating two types of nodules, cut off ADC value was determined at 1.1×10-3mm2s-1 and its sensitivity, specificity, PPV, NPV and diagnostic accuracy was 84.6, 95.4, 88.8, 91.5 and 92.3% respectively. Conclusion: Diffusion Weighted MRI is a non-invasive imaging investigation without ionizing radiation hazard. Its greater soft tissue differentiation and multiplanar images help in the diagnosis of malignant thyroid nodules with high sensitivity and accuracy. The overload of unnecessary surgeries is thus lowered when pre-operative FNAC is indecisive and aids in making a precise diagnosis.